2019
DOI: 10.1158/0008-5472.can-18-2799
|View full text |Cite
|
Sign up to set email alerts
|

An HK2 Antisense Oligonucleotide Induces Synthetic Lethality in HK1−HK2+ Multiple Myeloma

Abstract: A synthetically lethal precision medicine therapy for HK1-HK2+ multiple myeloma using an HK2 antisense oligonucleotide, metformin, and perhexiline. Most normal tissues Tolerated Tolerated HK1 + HK2 + multiple myeloma HK 2-A SO Me tfo rmi n Per hex ilin e HK1-HK2 + multiple myeloma Glucose-6-P Glucose-6-P Glucose Glucose HK1 HK2 HK2 Synthetically lethal Although the majority of adult tissues express only hexokinase 1 (HK1) for glycolysis, most cancers express hexokinase 2 (HK2) and many coexpress HK1 and HK2. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 25 publications
1
50
0
Order By: Relevance
“…The development of a specific inhibitor of HK2 may improve the prognosis of patients with refractory MM. Indeed, Xu et al 45 recently demonstrated the effectiveness of antisense oligos of HK2 against myeloma xenografted mice. However, because inhibition of the glycolytic system is also likely to damage normal tissues, it may be necessary to develop a drug delivery system that allows a HK2 inhibitor to exert its effect only in the bone marrow microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a specific inhibitor of HK2 may improve the prognosis of patients with refractory MM. Indeed, Xu et al 45 recently demonstrated the effectiveness of antisense oligos of HK2 against myeloma xenografted mice. However, because inhibition of the glycolytic system is also likely to damage normal tissues, it may be necessary to develop a drug delivery system that allows a HK2 inhibitor to exert its effect only in the bone marrow microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…HK2 overexpression is observed in many solid tumors, and is associated with a poor prognosis 29 . Most MM tumor cells express HK2 30 . Our analysis of two cohorts of MM patients further indicated that high HK2 levels were correlated with a shorter EFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological agents that target glucose metabolism are generally highly cytotoxic 32 . However, the knockdown of HK2 expression with an antisense oligonucleotide (HK2-ASO) has a strong cytostatic effect on MM cell lines and in xenograft models 30 . Interestingly, HK2-ASO acts in synergy with an inhibitor of mitochondrial complex I (metformin), both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Among HK family members, the expression of HK2 is relatively limited in normal adult tissues, including skeletal and adipose tissues, and HK2 is more catalytically efficient [ 9 ]. Moreover, HK2 is highly expressed in many tumor tissues and could be a potential target for antitumor therapy based on the promising results of preclinical studies [ 9 14 ].…”
Section: Introductionmentioning
confidence: 99%